Pre-exposure prophylaxis as an opportunity for engagement in HIV prevention among South African adolescents - Ashleigh LoVette; Caroline Kuo; Danielle Giovenco; Jacqueline Hoare; Kristen Underhill; Don Operario (Taylor & Francis Group, 2022)
Pre-exposure prophylaxis (PrEP) offers a potential biomedical strategy to reduce HIV incidence among adolescent populations disproportionately affected by HIV. There is limited evidence on the social and clinical implications, including engagement in HIV prevention efforts, of PrEP for South African adolescents, who face high HIV risk. We conducted a mixed-methods study in Western Cape, South Africa from 2015 to 2016. Adolescents (N = 35) aged 16-17 and clinical service providers working with adolescents (N = 25) were recruited from community and clinic settings. Adolescents and service providers completed a survey about their overall perceptions of PrEP and completed interviews guided by semi-structured protocols. We performed descriptive analysis of quantitative data using SPSS and thematic analysis of qualitative data using NVivo. The majority of adolescents endorsed future PrEP use for themselves and partners, and all clinical service providers endorsed future PrEP use for sexually active adolescents. Both adolescents and service providers identified PrEP as an opportunity to engage youth as active participants in HIV prevention. Service providers also viewed PrEP as a potential mechanism for shifting life trajectories. Findings from this study enhance our understanding of the considerations needed to engage adolescents and clinical service providers in the roll-out of oral PrEP in South Africa.